Local Language Interference on Non-Native Arabic Speaker in Rural Santri Communities: Sociolinguistic Study - Rohman, Abdul; Maksum, Ali; Wargadinata, Wildana; Taufiq, Ahmad (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
This study investigates the influence of local language (Madurese) interference on foreign language (Arabic) acquisition among rural Indonesian santri communities. Recognizing that traditional views often frame interference as a linguistic deficit, this research addresses a gap in the existing literature by exploring the deeper sociolinguistic dynamics and informal language use within rural pesantren settings. Specifically, it aims to analyze (1) forms of local language interference in Arabic, (2) factors causing such interference, and (3) its impact on santri speaking skills. Employing a qualitative-ethnographic design, the study collected data through naturalistic observation and unstructured interviews with 79 Madurese-speaking santri in Gondanglegi sub-district, East Java, analyzing them within a sociolinguistic framework grounded in interference theory and diglossia. Findings reveal significant phonological, morphological, syntactic, and lexical interference patterns demonstrably linked to the unique sociocultural context of pesantren multilingualism. Critically, these interferences are not merely errors but actively foster community, playfulness, and shared identity, thereby transforming Arabic into a more dynamic and engaging learning experience. This research offers a novel sociolinguistic analysis, arguing that interference in this context functions as an active strategy for religious pedagogy and cultural preservation. It expands translanguaging theory by highlighting the sacred-secular duality in language mixing—a phenomenon rarely documented in traditional Islamic education globally.